Sealing efficiency and safety of a polyurethane-based fecal management system in intensive care: results from a real-world study - Gutting, Tobias; Brobeil, Angelika; Strach, Lisa; Stricker, Elisabeth; Boxberger, Monica; Trierweiler-Hauke, Birgit; Heine, Clemens; Michl, Patrick; Luntz, Steffen P.; Robert, Bérénice; Göbel, Fred; Weis, Christiane; et al. (Australian critical care, 2025)
Objective - Fecal management systems (FMSs) are critical for preventing skin irritations and anal dermatitis in intensive care. A polyurethane-based system (hygh-tec® [Advanced Medical Balloons]) has been introduced in the European Union and United States. This real-world observational study aimed to evaluate the sealing efficiency and safety of the system in routine care. - Methods - Thirty-nine patients were included in the descriptive analysis (18 females and 21 males; mean age: 66.4 ± 10.5 years; body mass index: 28.8 ± 11.7 kg/m2). Intensive care nurses documented findings related to sealing efficiency, anal lesions, and adverse events during their shifts. - Results - Sealing efficiency was assessed from 1110 shift reports. The mean device usage duration was 10.8 days (range: 3-31 days). No visible perianal contamination was noted in 76.0% of shift reports (n = 844). Relevant leakage was documented in 10.7% of cases and was independent of body mass index, anal sphincter muscle tone, and reason for admission. Stool consistency and patient vigilance had minimal influence. There were no device-related adverse events, and the incidence of anal lesions was 0.8% over 31 days of use. - Conclusion - The polyurethane-based FMS demonstrated excellent sealing efficiency, tolerability, and safety. Controlled studies are needed to confirm these findings and evaluate economic implications. FMSs can improve both work quality and patient safety.